KAJIAN ECODESIGN LANSKAP PERMUKIMAN PERKOTAAN - Vina Pratiwi; Andi Gunawan; Indung Sitti Fatimah (Jurnal Lanskap Indonesia, 2014)
Harmony between settlement and environment is basis of ecological movement recent-ly. It is necessary to examine ecodesign criteria of settlement landscape. The objectives of study are identify critical component and ideal criteria of landscape ecodesign in urban settlement. In this study there was assessment of two settlements landscape as test-cases to illustrate the use of criterias that has been developed. Analytical Hierar-chy Process (AHP) was used as method to identify critical component. Result of AHP was used to assess test-cases and specify ideal criteria. The result showed critical com-ponent of landscape ecodesign in urban settlement is water (29.6%) and alternative priorities of landscape ecodesign is community participation (38.4%). The ecodesign accomplishment classified in high, moderate, and low level. Test-cases accomplishment was in moderate level (score 2.50 to 4.98). This result indicate both of regions has not fully implement ecodesign criteria. The ideal landscape ecodesign of settlement was maximum condition from sixteen subcomponents in design criteria.